What do extended cardiac surgical team members in the Kingdom of Saudi Arabia think about their jobs, and what would improve them? A qualitative study - Mohammed Shegafi; Mary Leamy; Geraldine Lee (Journal of Perioperative Nursing)
Despite the long history of integrating non-medical practitioners into the extended cardiac surgical team, concerns about job design that reduce job satisfaction persist in the literature. In the Kingdom of Saudi Arabia (KSA), previous research has found that these non-medical practitioners known as cardiac surgical assistants (SAs) express significant dissatisfaction with multiple aspects of their role. Improving job satisfaction can positively impact on the recruitment and retention of this valuable workforce who increase surgical capacity within cardiac units. This qualitative study was therefore conducted to gain an in-depth understanding of cardiac SAs’ perspectives of their role and to explore how it could be redesigned to improve their job satisfaction. Through thematic analysis of 14 individual interviews, six themes were identified: the importance of the role, low level of autonomy, lack of recognition, inconsistency of training, poor appraisal and feedback, and feeling unappreciated and undervalued. The data allowed a number of specific recommendations to be formulated that could be implemented at service, organisational and professional levels to enhance SA job satisfaction. It is important that the working conditions of surgical assistants should be further improved to address the issues which cause lower levels of motivation and a greater intention to leave their role.